A preliminary analysis on gender aspects in transport systems and mobility services: presentation of a survey design - Pirra, M. (2021)
As sustainability is becoming a common practice in planning transport systems and mobility services, the designation and management of gender issues are of paramount importance. TInnGO is a European Project that has developed a network of 10 national Hubs to build the capacity to generate and apply evidence on gender equality and transport issues at the European level. This paper presents the project activities by introducing a relevant framework and exploring user mobility experiences based on gender to identify diversified needs and requirements. This process relies on the combination of a review of current gender-oriented experiences and practices in mobility with focus group activities conducted in four different EU cities. The insights obtained from these activities supported the design of a survey to collect information on socioeconomic, personal, and operational aspects to serve a gender-oriented transport analysis for all the Hubs. These preliminary analyses identified the main issues related to the female mobility experience, namely safety, security, accessibility, and transport reliability. Future research on the data collected through the survey would help operators in successfully improving their mobility offer to women.